Insights on hydrogen bond assisted solvent selection in certain acid–base heterogeneous catalysis through acceptor and donor numbers. Issue 4 (24th December 2020) - Marakatti, Vijaykumar S.; Klimeš, Jiří; Kasinathan, Palraj; Sorathia, Kesha; Tew, David P.; Gaigneaux, Eric M.
Abstract : Acceptor and donor numbers as efficient tools for the selection of solvents in certain acid–base heterogeneous catalysis; role of the hydrogen bond. Abstract : The choice of an appropriate solvent in heterogeneous catalysis is not always straightforward but it affects significantly the activity and selectivity in organic reactions. Here we show that the acceptor number (AN) and donor number (DN) make the selection of solvent robust and competitive compared to traditional solvent properties such as dielectric constant, polarity and nature. The conversion rates measured in selected acid or base-catalysed reactions in the liquid phase (alkylation, acylation, esterification, condensation) consistently vary with the AN or DN of the solvents in which they are achieved. The impact of the AN and DN in these reactions was understood by addressing the interactions between the catalyst, solvents, and reactants through spectroscopic (FTIR and UV-vis) techniques and DFT simulations. The association between the AN and DN, and the catalytic performance is shown to proceed via the strength of the non-covalent hydrogen bond established between the partners of the reaction. The strength of hydrogen bonds of the solvent with the catalyst influences the acid sites of the catalyst directly and by this means plays a crucial role during the reaction. These findings build strong fundamental scientific information on the solvent effects in heterogeneous catalysis.